An efficient synthesis of (+/-)-panduratin A and (+/-)-isopanduratin A, inhibitors of dengue-2 viral activity - Chee, Chin Fei; Abdullah, Iskandar; Buckle, Michael James Christopher; Abd Rahman, Noorsaadah (Elsevier, 2010)
Panduratin A and its regioisomer isopanduratin A are synthesized in four steps from (E)-ocimene, [(E)-3,7-dimethyl-1,3,6-octatriene] via a Diels-Alder cycloaddition reaction. (C) 2009 Elsevier Ltd. All rights reserved.